COVID-19 pandemic: maker or breaker for families having children with autism spectrum disorder-case series of maternal experiences, strategies and suggestions - Inamdar, Nusrat R.; Wade, Minal R.; Mauskar , Anupama V. (International Journal of Contemporary Pediatrics, 2024)
The COVID-19 pandemic due to prioritization of emergency and COVID-19 patient care at hospitals and disruption of daily routines and finances, impacted significantly families having people with special needs. This case series highlights the problems faced and strategies used by mothers of children having autism spectrum disorder (ASD). It summarizes the experiences of nine families of ASD children (2 to 9 years), selected consecutively from pediatric developmental/disability outpatient department (OPD) of a tertiary care center during i.e. April 2021 to May 2021 (2nd wave of COVID-19 pandemic) using a pre-designed proforma. Socio-demographic details, maternal experiences about challenges faced in child’s home care, special therapies, managing child’s behaviour, family support system, adaptations and their suggestions were recorded. The age group was 2 to 9 years and 8 were males. 7 out of 9 mothers reported that their child’s interaction with father and other family members improved. Institutional therapy was discontinued by all mothers. Two mothers reported increased aggression in the child. Mothers from joint family and having supportive families reported less stress. Children who had company of parents/grandparents/sibling and availability of indoor games, art and craft and storytelling, reported less screen time and less behavioural disturbances though all the mothers reported increased screen time compared to pre COVID times. Mother’s empowerment is key to success. Indoor physical games, unstructured play, increasing social awareness, supportive families, tele-rehabilitation services can improve overall progress in ASD children. Health care practices need to be revised from time to time for special needs/situations.